Tree nut allergies: Allergen homology, cross‐reactivity, and implications for therapy. Issue 7 (4th June 2018) - Smeekens, J. M.; Bagley, K.; Kulis, M.
Summary: Tree nut allergy is a potentially life‐threatening disease that is increasing in prevalence, now affecting 1% of the general population in the United States. While other food allergies often resolve spontaneously, tree nut allergies are outgrown in less than 10% of cases. Due to the likelihood of cross‐sensitization to multiple tree nut allergens, the current treatment guideline is strict avoidance of all nuts once one tree nut allergy has been diagnosed. For example, walnut and pecan are highly cross‐reactive, along with cashew and pistachio, but the extent of clinical, IgE‐mediated cross‐reactivity among other tree nuts remains unclear, therefore making avoidance of all tree nuts a safe approach. There have been recent advances in immunotherapy for food allergies. For instance, there are investigational immunotherapies for milk, egg and peanut allergies, specifically oral immunotherapy, sublingual immunotherapy and epicutaneous immunotherapy. However, there are no large randomized controlled clinical trials for tree nut allergies. Even though there has been less research into tree nut allergy immunotherapies, the evidence of T‐cell cross‐reactivity among tree nuts exists in animal models and in T cells from allergic patients indicates that immunotherapeutic interventions may be possible. Here, we review the literature regarding epidemiology, allergen homology and cross‐reactivity among tree nuts, and explore how current findings can be employed for effective therapy.